Urban leisure: yacht clubs in the social and cultural space of Belarusian provinces in the late 19th – early 20th century - Busko, Siarhei I. (Journal of the Belarusian State University. History, 2022)
The article is devoted to the history of yacht clubs on the territory of Belarus at the turn of the 19th – 20th centuries. The author examines the conditions for their emergence, the main statutory documents, key areas of activity, changes in the social composition and place in the structure of urban leisure during 1895–1915. The article also presents attempts to create yacht clubs, reflecting the social demand of the urban population, but not implemented for objective reasons. Attention is paid to the transformation of these public organisations from narrow-profile elite clubs to the centres of cultural and sports life in the Belarusian city.